A review of the ban on tobacco smoking in public universities in Malaysia / Imran Ismail and Muhd Nabil Fikri Mat Aji - Ismail, Imran; Mat Aji, Muhd Nabil Fikri (2007)
In Malaysia smoking ban is imposed in all public areas such as hospitals and government departments and public universities. The purpose of this research is to examine the relevant laws on smoking bans in Malaysia with relevance to smoking in public universities. This is due to the fact that despite the ban being in place smokers continue to smoke in these places. Therefore it can be concluded that either the law is not effective because of lack of enforcement or the public is just not aware of the ban. This research will look upon the law on the ban of smoking in Malaysia and other countries. This research is limited to Institutions of higher learning in the Klang Valley. Regulations made by other universities will also be examined. It is common knowledge that smoking brings adverse effects to smokers and non smokers. Thus, this is one of the reasons for the ban on smoking in public areas including the public the universities. This research will analyse the ban on smoking and discuss whether the ban has been effective.